Penjadwalan Ulang Proyek Peningkatan Jalan Bulu – Jatirogo (Lanjutan) Kabupaten Tuban dengan Menggunakan Metode LSM (Linear Scheduling Method) - Evi Kumalasari; Sugeng Dwi Hartantiyo; Yosef Cahyo (Jurnal Talenta Sipil, 2026)
One of the main indicators of project success is the completion of work according to schedule. Inaccuracy in scheduling can result in delays or cost overruns. Therefore, scheduling is a crucial element in the sequence of project implementation. This study aims to calculate the project duration using the LSM method and to determine which is more effective between scheduling with the LSM (Linear Scheduling Method) and the existing method. The research employs a quantitative approach focusing on the collection and analysis of measurable and countable variables to obtain objective results, and applies a mathematical approach. Microsoft Excel software was utilized as a tool to recalculate the project execution duration and to develop linear charts based on groups of activities with linear characteristics. The analysis results show that for the Bulu–Jatirogo Road Improvement Project (continuation) in Tuban Regency, the use of the Linear Scheduling method can shorten the project duration to 50 days, which is significantly more efficient compared to the previous method that required 110 days. This 60-day difference indicates that the Linear Scheduling method is superior in the effectiveness of schedule planning.